Prevalence of Lumbosacral Transitional Vertebral Anomalies Among Healthy Volunteers and Patients with Hip Pathology: Association with Spinopelvic Characteristics. Issue 1 (22nd January 2023) - Verhaegen, Jeroen C.F.; Alves Batista, Nuno; Horton, Isabel; Rakhra, Kawan; Beaulé, Paul E.; Michielsen, Jozef; Stratton, Alexandra; Grammatopoulos, George
Abstract : Background: A lumbosacral transitional vertebra (LSTV) has been reported to be prevalent among patients with hip dysplasia. The aims of this study were to determine the (1) prevalence of an LSTV in young patients presenting with hip pain and a group of asymptomatic volunteers, (2) effect of an LSTV on spinopelvic characteristics, and (3) presence of low back pain among patients with an LSTV. Methods: This cross-sectional study included 102 patients with hip pathology and 51 asymptomatic volunteers (mean age, 33.9 ± 7.3 years; mean body mass index, 26.0 ± 5.0 kg/m 2 ; 57.5% female). Participants underwent radiographic assessment of the lumbar spine and pelvis in standing and deep-seated positions. LSTV occurrence was classified according to the Castellvi system. Spinopelvic characteristics included lumbar lordosis (including segmental lumbar angles), pelvic tilt, and hip flexion (pelvic-femoral angle). Differences between standing and deep-seated values were calculated. Low back pain was assessed using the Oswestry Disability Index. Results: The prevalence of LSTV type ≥II was 8.5%, with no difference between patients and volunteers (p = 0.386). Individuals with an LSTV had a greater standing L1-L5 angle (mean, 51.6° ± 11.7° versus 38.9° ± 9.3°; p < 0.001). The overall spinal flexion (change in L1-S1 angle between the standing and deep-seated positions) in individuals with an LSTV was similar to that in individuals without an LSTV; restricted L5-S1 mobility was compensated for at L1-L2 (10.2° ± 5.8° in those with versus 8.4° ± 4.1° in those without an LSTV; p = 0.070). No significant difference in the presence of low back pain was found (p = 0.250). Conclusions: An LSTV was found in 8.5% of young adults, with no difference between patients with hip pathology and controls. Individuals with an LSTV have greater standing lumbar lordosis, with altered mechanics at the cephalad adjacent level, which may predispose these individuals to degenerative changes at this level. Level of Evidence: Prognostic Level II . See Instructions for Authors for a complete description of levels of evidence.